Deletion of the Wilms’ Tumor Suppressor Gene in the Cardiac Troponin-T Lineage Reveals Novel Functions of WT1 in Heart Development - Díaz del Moral, Sandra; Barrena, Silvia; Hernández-Torres, Francisco; Aránega, Amelia; Villaescusa, José Manuel; Gómez Doblas, Juan José; Franco, Diego; Jiménez-Navarro, Manuel; Muñoz-Chápuli, Ramón; Carmona, Rita (Frontiers in Cell and Developmental Biology, 2021)
Expression of Wilms’ tumor suppressor transcription factor (WT1) in the embryonic epicardium is essential for cardiac development, but its myocardial expression is little known. We have found that WT1 is expressed at low levels in 20-25% of the embryonic cardiomyocytes. Conditional ablation of WT1 using a cardiac troponin T driver (Tnnt2Cre) caused abnormal sinus venosus and atrium development, lack of pectinate muscles, thin ventricular myocardium and, in some cases, interventricular septum and cardiac wall defects, ventricular diverticula and aneurisms. Coronary development was normal and there was not embryonic lethality, although survival of adult mutant mice was reduced probably due to perinatal mortality. Adult mutant mice showed electrocardiographic anomalies, including increased RR and QRS intervals, and decreased PR intervals. RNASeq analysis identified differential expression of 137 genes in the E13.5 mutant heart as compared to controls. GO functional enrichment analysis suggested that both calcium ion regulation and modulation of potassium channels are deeply altered in the mutant myocardium. In summary, together with its essential function in the embryonic epicardium, myocardial WT1 expression is also required for normal cardiac development.